Amsterdam koopt kunst : Gemeentelije Kunstaankopen 1985. (Amsterdam : Museum Fodor, 1986)
Bien, Waldo ; Bijlenga, Marian ; Blake, John ; Blanca, Paul ; Botma, Akke ; Capelle, Herbert ; Cardena, Michel ; Colton, Adam ; Dalstra, Koos ; Derrez, Paul ; Dilworth, Norman ; Driessen, Maya ; van Elden, Barten ; van Es, Hannes ; Fortuyn/O'Brien ; Garcia, David ; van Gool, Jano ; Goulart, Claudio ; Groot, Mieke ; de Groot, Mieke ; Gudmundsson, Sigurdur ; Heyink, Harry ; Hoover, Nan ; Hooykaas, Madelon ; Ikelaar, Jan Gerrit ; Jacklin, Michael ; Jorna, Johan ; Kleerebezem, Jouke ; van Winsen, Dok ; Kruit, Jos ; Kurpershoek, Reinier ; Lap, Geert ; Lichtveld, Alexander ; Lotsy, Henk ; Luik, Hieke ; Marinus, Kees ; Mout, Wout ; Pallesen, Liesbeth ; Planteydt, Annelies ; Postma, Tom ; Puckey, Tom ; Putte, Loes Van Den ; Reyers, Steven ; Rolf, Johnny ; Saretsky, Bob ; Schabracq, Alexander ; Servaas ; Shaw, Tim ; Sluik, Ron ; Smit, Robert ; van der Spek, Arjanne ; Stansfield, Elsa ; Strijker, Annie ; Thorkelsdóttir, Rúna ; Tüzüner, Isik Andreas ; Urdarianu, Veron ; Vonck, Irene ; Vroegindeweij, Leo ; Wright, Annie
biog., tent. per kunstenaar
Amsterdam koopt kunst : Gemeentelijke Kunstaankopen 1985, Museum Fodor, Amsterdam, 08.03.1986 - 07.04.1986
Nederlands & Engels
boek
Keywords: Amsterdam